Can the use of azithromycin during labour reduce the incidence of infection among puerperae and newborns? A systematic review and meta-analysis of randomized controlled trials - Haiyan Ye; Jinlu Hu; Bo Li; Xia Yu; Xuemei Zheng (BMC, 2024)
Abstract Objective This systematic review and meta-analysis investigated whether the use of azithromycin during labour or caesarean section reduces the incidence of sepsis and infection among mothers and newborns. Data sources We independently searched the PubMed, Web of Science, Cochrane Library and EMBASE databases for relevant studies published before February, 2024. Methods We included RCTs that evaluated the effect of prenatal oral or intravenous azithromycin or placebo on intrapartum or postpartum infection incidence. We included studies evaluating women who had vaginal births as well as caesarean sections. Studies reporting maternal and neonatal infections were included in the current analysis. Review Manager 5.4 was used to analyse 6 randomized clinical trials involving 44,448 mothers and 44,820 newborns. The risk of bias of each included study was assessed using the criteria outlined in the Cochrane Handbook for Systematic Reviews of Interventions.Primary outcomes included the incidence of maternal sepsis and all-cause mortality and neonatal sepsis and all-cause mortality; secondary outcomes included maternal (endometritis, wound and surgical site infections, chorioamnionitis, and urinary tract infections) and neonatal outcomes (infections of the eyes, ears and skin). A random-effects model was used to test for overall effects and heterogeneity. Results The pooled odds ratios (ORs) were as follows: 0.65 for maternal sepsis (95% CI, 0.55-0.77; I 2 , 0%; P < .00001); 0.62 for endometritis (95% CI, 0.52-0.74; I 2, 2%; P < .00001); and 0.43 for maternal wound or surgical site infection (95% CI, 0.24-0.78; P < .005); however, there was great heterogeneity among the studies (I 2, 75%). The pooled OR for pyelonephritis and urinary tract infections was 0.3 (95% CI, 0.17-0.52; I 2, 0%; P < .0001), and that for neonatal skin infections was 0.48 (95% CI, 0.35-0.65; I 2, 0%, P < .00001). There was no significant difference in maternal all-cause mortality or incidence of chorioamnionitis between the two groups. No significant differences were observed in the incidence of neonatal sepsis or suspected sepsis, all-cause mortality, or infections of the eyes or ears. Conclusion In this meta-analysis, azithromycin use during labour reduced the incidence of maternal sepsis, endometritis, incisional infections and urinary tract infections but did not reduce the incidence of neonatal-associated infections, except for neonatal skin infections. These findings indicate that azithromycin may be potentially beneficial for maternal postpartum infections, but its effect on neonatal prognosis remains unclear. Azithromycin should be used antenatally only if the clinical indication is clear and the potential benefits outweigh the harms.